Alterations of the endocannabinoid system and circulating and peripheral tissue levels of endocannabinoids in sarcopenic rats. Issue 1 (2nd December 2021) - Le Bacquer, Olivier; Salles, Jérôme; Piscitelli, Fabiana; Sanchez, Phelipe; Martin, Vincent; Montaurier, Christophe; Di Marzo, Vincenzo; Walrand, Stéphane
Abstract: Background: Activation of the endocannabinoid system (ECS) is associated with the development of obesity and insulin resistance, and with perturbed skeletal muscle development. Age‐related sarcopenia is a progressive and generalized skeletal muscle disorder involving an accelerated loss of muscle mass and function, with changes in skeletal muscle protein homeostasis due to lipid accumulation and anabolic resistance. Hence, both obesity and sarcopenia share a common set of pathophysiological alterations leading to skeletal muscle impairment. The aim of this study was to characterize how sarcopenia impacts the ECS and if these modifications were related to the loss of muscle mass and function associated with aging in rats. Methods: Six‐month‐old and 24‐month‐old male rats were used to measure the contractile properties of the plantarflexors (isometric torque–frequency relationship & concentric power–velocity relationship) and to evaluate locomotor activity, motor coordination, and voluntary gait by open field, rotarod, and catwalk tests, respectively. Levels of endocannabinoids (AEA & 2‐AG) and endocannabinoid‐like molecules (OEA & PEA) were measured by LCF‐MS/MS in plasma, skeletal muscle, and adipose tissue, while the expression of genes coding for the ECS were investigated by quantitative reverse transcription PCR (RT‐qPCR). Results: Sarcopenia in old rats was exemplified by a 49% decrease in hindlimb muscle mass ( P < 0.01), which was associated with severe impairment of isometric torque, power, voluntary locomotor activity, motor coordination, and gait quality. Sarcopenia was associated with (1) increased 2‐AG (+32%, P = 0.07) and reduced PEA and OEA levels in the plasma (−25% and −40%, respectively, P < 0.01); (2) an increased content of AEA, PEA, and OEA in subcutaneous adipose tissue ( P < 0.01); and (3) a four‐fold increase of 2‐AG content in the soleus ( P < 0.01) and a reduced OEA content in EDL (−80%, P < 0.01). These alterations were associated with profound modifications in the expression of the ECS genes in the adipose tissue and skeletal muscle. Conclusions: Taken together, these findings demonstrate that circulating and peripheral tissue endocannabinoid tone are altered in sarcopenia. They also demonstrate that OEA plasma levels are associated with skeletal muscle function and loss of locomotor activity in rats, suggesting OEA could be used as a circulating biomarker for sarcopenia.